Поселення пізньозарубинецького часу в Харкові - Заднiков, С.А. (Археологія, 2019)
У 2007 р. у м. Харків було виявлено нове поселення початку І тис н. е., на якому проведено рятівні археологічні дослідження. Досліджено 102 м² , з’ясовано потужність культурного шару на різних ділянках, виявлено дві господарські ями та уламки кераміки пізньозарубинецького часу. Керамічний комплекс та великий відсоток лощеного посуду, знайденого під час дослідження, характерний для пам’яток типу Картамишево-2–Тернівка-2. Таким чином, розкоп дозволив отримати певне уявлення про життя давнього населення та зафіксувати місце розташування однієї із садиб І—ІІ ст. н. е. В 2007 году в северной части города Харькова, в урочище Саржин Яр при проведении археологической экспертизы земельного участка было выявлено новое поселение «Саржин Яр-3», которое относится к началу І тыс. н. э. Поселение находиться на правом склоне балки Саржин Яр, по дну которой протекает ручей Саржинка. Судя по рельефу, с запада и востока поселение ограничивается небольшими ярками, а с юга — дном балки. Ориентировочные размеры поселения составляют 200 × 150 м. К сожалению, большая часть поселения застроена и разрушена. Через поселение проходит ул. Деревянко, которая на этом участке была сделана из насыпного грунта, часть поселения находится под территорией гаражного кооператива. С целью получения большей информации в 2007 г. под руководством автора в разных частях поселения было заложено три раскопа общей площадью 102 м² . Культурный слой очень сильно разрушен и только в некоторых местах он сохранился на толщину 0,10—0,25 м. В раскопе 1 было обнаружено две хозяйственные ямы, содержащие выразительные культурные остатки. За пределами комплексов фрагменты керамики очень редко встречались. Керамический комплекс раскопа представлен обломками лепных горшков с шероховатой (грубой) поверхностью. Среди них выделяются два типа горшков: биконические (или ребристые) и круглобокие. Один горшок имеет форму банки. Среди мисок, края бортика которых загнуты внутрь, можно выделить два типа: с ребром и без него (с плавным профилем). Одна миска имеет отогнутый наружу край. В заполнении ям были найдены обломки двух дисков. Всего при раскопках найдено 258 фрагментов керамики, из них 229 фрагментов горшков с грубой поверхностью, что составляет 89 %; лощеной посуды — 29 обломков (11 %). Подобные горшки и миски были найдены на поселениях Картамышево-2—Терновка-2, Головино-1 и других памятниках позднезарубинецкого времени. На этих поселениях процент лощеной посуды составляет более 4,0 % от общего количества обломков посуды. И так, процент лощеной посуды и керамический комплекс характерны для памятников типа Картамышево-2— Терновка-2. Таким образом, в 2007 г. в г. Харьков, в уроч. Саржин Яр обнаружено новое поселение, на котором открыты остатки жилищно-хозяйственных комплексов второй половины I—II ст. н. э. In 2007, in the northern part of Kharkiv, in the Sarzhyn Yar hole, during the archaeological examination of the land, a new settlement “Sarzhyn Yar-3” was discovered that is dated to the beginning of 1st millennium AD. The settlement is located on the right slope of Sarzhyn Yar ravine, along the bottom of which flows stream Sarzhynka. Judging by the relief, from the west and east the settlement is limited by small ravines, and from the south by the bottom of the ravine. The approximate size of the settlement is 200 × 150 m. Unfortunately, most of the settlement is built up and destroyed. Through the settlement passes st. Derevianko, which at this part was made of bulk soil. One section of the settlement is located under the territory of the garage cooperative. In order to obtain more information in 2007, three excavations with a total area of 102 square meters were laid in different parts of the settlement under the supervision of the author. The cultural layer is very much destroyed and only in some places it was preserved to a thickness of 0,10—0,25 m. In excavation No. 1, two household pits were found containing expressive cultural remains. Outside the complexes, fragments of ceramics are very rare. The ceramic complex of the excavation is represented by fragments of molded pots with a rough surface. Two types of pots stand out among them: biconical (or ribbed) and round-sided. One pot is jar-shaped. Among the bowls, the edges of the rim of which are bent inward, two types can be distinguished: with and without a rib (with a smooth profile). One bowl has a rim bent outward. In the filling of the pits, fragments of two discs were found. In total, 258 fragments of ceramics were found during excavations, of which 229 fragments of pots with a rough surface, which is 89%. Burnished bowls — 29 fragments (11 %). Such pots and bowls were found in the settlements of Kartamyshevo-2 —Ternovka-2, Golovino-1 and other monuments of the late Zarubynets culture. At these settlements, the percentage of burnished bowls is more than 4,0 % of the total number of pottery fragments. Thus, the percentage of burnished pottery and the ceramic complex are typical for monuments of Kartamyshevo-2—Ternovka-2 types. Thereby, in 2007, in Kharkiv, in the Sarzhyn Yar hole, a new settlement was discovered, at which the remains of housing complexes of the second half of 1st—2nd c. AD were studied.